Borane-catalyzed cross-metathesis strategy for facile transformation of cyclic (alkyl)(amino)germylenes - Rao, Bin (2021)
A borane B(C6 F5 )3 -catalyzed metathesis reaction between the Si-C bond in the cyclic (alkyl)(amino)germylene (CAAGe) 1 and the Si-H bond in a silane (R3 SiH; 2) is reported. Mechanistic studies propose that the initial step of the reaction involves Si-H bond activation to furnish an ionic species [1-SiR3 ]+ [HB(C6 F5 )3 ]- , from which [Me3 Si]+ [HB(C6 F5 )3 ]- and an azagermole intermediate are generated. The former yields Me3 SiH concomitant with the regeneration of B(C6 F5 )3 whereas the latter undergoes isomerization to afford CAAGes bearing various silyl groups on the carbon atom next to the germylene center. This strategy allows the straightforward synthesis of eight new CAAGes starting from 1.